TIPE SEMANTIK ADJEKTIVA BAHASA MELAYU MANADO - Armiati Rasyid (Balai Bahasa Provinsi Papua, 2019)
This paper describes the semantic types and components of meaning distinguishing adjective interlexeme in Manado Malay. This is a qualitative descriptive study. Research data collection is done by observation, elicitation, interviews, and triangulation technique. Data are analyzed by analysis components of meaning by Nida. The adjective semantic types found in Manado Malay is (1) adjective lexeme of attitude, character, (2) which states lexeme form, (3) which states lexeme size, (4) which states lexeme time/age, (5 ) lexemes which express color, (6) which states lexeme distance, (7) which states lexeme power/energy, (8) which states lexeme way, and (9) which states lexeme meaning sensory perception or impression of assessment. Based on the semantic type, it is found interlexeme distinguishing components of meaning in general depends on the referent referred to, for example, humans, men, women, objects, animals, the value of a sense of language. Kata-kata kunci: leksem, adjektiva, tipe semantik, komponen makna